1979
DOI: 10.1093/nar/7.8.2303
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of somatic vs germ cell DNAs analyzed by restriction endonuclease digestions

Abstract: Bacterial restriction endonucleases containing the dinucleotide CpG in their cleavage sequences were used to compare the methylation patterns of primarily repeated DNA sequences in (1) bovine somatic cell native DNAs vs bovine sperm cell native DNA and (2) native vs renatured bovine liver and sperm cell DNAs. The restriction patterns of sperm native DNA differ markedly from those of somatic cell native DNAs when using Hpa II, Hha I, and Ava I but not when using the enzymes Eco RI and Msp I. Digestion patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 26 publications
3
22
0
2
Order By: Relevance
“…In conformity with a previous report (10) we found that thymus DNA contains about 1.5 times as much m5 Cyt as sperm DNA. However, at least for the MspI/HpaII sites tested, this difference is not due to hemimethylation.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…In conformity with a previous report (10) we found that thymus DNA contains about 1.5 times as much m5 Cyt as sperm DNA. However, at least for the MspI/HpaII sites tested, this difference is not due to hemimethylation.…”
Section: Introductionsupporting
confidence: 93%
“…With these ideas in mind we have examined the DNA of bovine thymus and sperm to test a hypothesis that the reduced methylation of some mammalian sperm DNAs might be explained by strand asynmnetric hemimethylation (10).…”
Section: Introductionmentioning
confidence: 99%
“…7 x 10'0 becquerels), (2)(3)(4)(5) ,g of DNA, and 1-2 units ofthe enzyme was incubated at 37°C for 1 hr. After further incubation in the presence of 7 ,g of protease K and 0.4% sodium dodecyl sulfate, the solution was made 0.4 M NaOH and incubated at 60°C for 30 min to destroy any RNAs that might possibly be methylated with contaminating RNA methyltransferase (5). The whole reaction mixture was then neutralized with HCl and extracted with phenol.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of tissue-specific methylation has been described (7)(8)(9), although the significance of the observed methylation patterns is unclear. A function in the regulation of gene expression is suggested especially by the effect of hypomethylation on globin synthesis in Friend cells (10) and the effect of azacytidine on differentiation (11,12).…”
mentioning
confidence: 99%
“…This requires efficient strategies for the detection of 5mC. Different concepts for discriminating between cytosine (C) and 5mC have been described which rely on endonuclease digestion,8 affinity enrichment,9 nanopore sequencing,10 different chemical behavior concerning redox reactivity,11 or selective deamination of C using sodium bisulfite 12…”
mentioning
confidence: 99%